In-situ growth Cu-Ni alloy nanowire and preparation method thereof

By constructing Cu-Ni alloy nanowires in situ on the gas diffusion layer, using the interaction between Cu and Ni atoms, the problems of high kinetic barriers and stable adsorption of intermediates in the C-C coupling process were solved, and efficient electrochemical reduction of CO2 was achieved, and the Faraday efficiency of producing C2H4 reached 46.98%.

CN119571366AActive Publication Date: 2025-03-07CHINA UNIV OF PETROLEUM (BEIJING)
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411702474.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-03-07
Estimated Expiration
2044-11-26

AI Technical Summary

Technical Problem

The prior art is difficult to efficiently convert CO2 into polycarbon products such as ethylene (C2H4), while copper-based catalysts have problems with high kinetic barriers and stable adsorption of intermediates during the C-C coupling process.

Method used

By constructing Cu-Ni alloy nanowires in situ on the gas diffusion layer (GDL), using the interaction between Cu and Ni atoms to improve the efficiency of C-C coupling, and electrochemical reduction is performed using a collaborative method of non-precious metals.

Benefits of technology

High-efficiency electrochemical reduction of CO2 was achieved, the Faraday efficiency of C2H4 was reached 46.98%, and the current density reached 231.81mA/cm2, which significantly improved the selectivity and stability of C2H4.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention discloses an in-situ growth Cu-Ni alloy nanowire and a preparation method of the in-situ growth Cu-Ni alloy nanowire. The preparation method of the Cu-Ni alloy nanowire comprises the following steps that S1, carbon paper is immersed in a mixed solution of CuSO4, NiCl2 and NiSO4 to be subjected to electro-deposition, and a Cu-Ni thin film is obtained; s2, the Cu-Ni thin film is subjected to a reaction under the alkaline condition, and a Cu-Ni hydroxide nanowire is obtained; s3, the Cu-Ni hydroxide nanowire is subjected to annealing, and a Cu-Ni oxide nanowire is obtained; and S4, the Cu-Ni oxide nanowire is subjected to electrochemical reduction, and the in-situ growth Cu-Ni alloy nanowire is obtained. According to the method, the Cu-Ni alloy nanowire grows on the carbon paper in situ to serve as a gas diffusion electrode, CO2 can be electrochemically reduced to prepare C2H4, the Faraday efficiency (FE) of C2H4 production reaches 46.98%, the current density reaches 231.81 mA / cm < 2 >, and the Faraday efficiency (FE) of C2H4 production obviously exceeds that of a bare copper nanowire (Cu NWs, 25.33%). The Cu-Ni alloy nanowire disclosed by the invention shows excellent stability by virtue of in-situ construction on the carbon paper, and can operate for more than 8 hours under high current.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an in-situ grown Cu-Ni alloy nanowire and a preparation method thereof, belonging to the technical field of electrocatalysis. Background Art

[0002] Converting CO2 into valuable industrial products via electrocatalytic processes is an important approach for sustainable development. In particular, reducing CO2 to fuels and industrial feedstocks can not only alleviate energy problems but also achieve the closure of the carbon cycle and provide a viable solution for carbon neutrality. Therefore, it is very important to design and fabricate high-performance electrocatalysts for specific high-value-added products. In recent years, researchers have made significant progress in developing electrocatalysts, ultimately achieving high conversion efficiencies of carbon monoxide (CO), formic acid (HCOOH), methane (CH4), and other C1 products. Nevertheless, the conversion of CO2 into multi-carbon products (C2) such as ethylene (C2H4) and ethanol (C2H5OH) remains a daunting challenge. C2H4 is known for its high energy density and, as a key compound, occupies an important strategic position in industrial gases. Metal catalysts, including Au, Ag, Sn, Ni, and Pb, show a tendency to generate C1 products. Uniquely, copper-based catalysts have demonstrated the ability to convert CO2 into C2H4 via a CC coupling process. However, the efficient conversion of C2H4 is hampered by the high kinetic barrier of the CC coupling process on the Cu catalyst surface and the stable adsorption of key intermediates. There are many strategies, such as crystal surface regulation, single atom, defect engineering, etc., to regulate the physical or chemical properties of catalysts to improve the adsorption and desorption processes. Researchers have designed a series of alloy catalysts such as Au-Cu and Ag-Cu, which enhance CC coupling through the CO spillover effect, thereby greatly improving the selectivity and efficiency of Cu metal in C2H4 production. Nevertheless, in order to reduce the application cost, it is necessary to free ourselves from the dependence on precious metals. Researchers have advanced the development of alloy materials such as Cu-Zn, Cu-Sn and Cu-Pd, but the catalytic results have not met high expectations. The present invention is specially proposed. Summary of the invention

[0003] The purpose of the present invention is to provide an in-situ grown Cu-Ni alloy nanowire, the interaction between Cu and Ni atoms significantly improves the efficiency of CC coupling, and has excellent C2H4 selectivity and stability.

[0004] The present invention adopts a synergistic approach of non-precious metals and performs in-situ construction of Cu-Ni alloy nanowire structures on a gas diffusion layer (GDL), which can electrochemically reduce CO2 to C2H4 and CO, showing excellent selectivity and stability.

[0005] The method for preparing Cu-Ni alloy nanowires provided by the present invention comprises the following steps: S1, immersing carbon paper in a mixed solution of CuSO4, NiCl2, and NiSO4 for electrodeposition to obtain a Cu-Ni film; S2, the Cu-Ni film reacts under alkaline conditions to obtain Cu-Ni hydroxide nanowires; S3, annealing the Cu-Ni hydroxide nanowires to obtain Cu-Ni oxide nanowires; S4. The Cu-Ni oxide nanowires are electrochemically reduced to obtain in-situ grown Cu-Ni alloy nanowires.

[0006] In the preparation method of the present invention, in step S1, the mixed solution is prepared from 0.1 M citric acid buffer.

[0007] In the preparation method of the present invention, in step S1, in the mixed solution, the concentration of CuSO4 is 0.05M-0.15M, the concentration of NiCl2 is 0.03M-0.08M, and the concentration of NiSO4 is 0.03M-0.08M.

[0008] In the preparation method of the present invention, in step S1, the electrodeposition time is 1500-2000s, and the obtained film is thoroughly dried in a nitrogen atmosphere.

[0009] In the preparation method of the present invention, in step S2, the alkaline condition is an aqueous solution of NaOH and (NH4)2S2O8, the concentration of NaOH is 45-50 g / L, and the concentration of (NH4)2S2O8 is 20-25 g / L.

[0010] In the preparation method of the present invention, in step S2, the reaction temperature is 2-8°C and the reaction time is 0.3-0.6h.

[0011] In the preparation method of the present invention, in step S3, the annealing temperature is 150-200° C., the time is 0.5-2 h, and the annealing is performed in a muffle furnace.

[0012] In the preparation method of the present invention, in step S4, the electrochemical reduction is performed in a flowing electrolytic cell using a 0.50 M sodium sulfate solution as an electrolyte, and a potential of -1.0 V (vs Ag / AgCl sat. KCl) may be applied for the electrochemical reduction.

[0013] The in-situ grown Cu-Ni alloy nanowires prepared by the method of the present invention can be used as gas diffusion electrodes to electrochemically reduce C2H4 and CO. The Faradaic efficiency (FE) of producing C2H4 reaches 46.98% and the current density reaches 231.81 mA / cm 2, significantly exceeding bare copper nanowires (Cu NWs, 25.33%). The Cu-Ni alloy nanowires of the present invention exhibit excellent stability by virtue of in-situ construction on the gas diffusion electrode, and can operate for more than 8 hours at high current. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 This is an electron microscope photograph of the Cu-Ni film prepared in Example 1 of the present invention.

[0015] Figure 2 This is an electron microscope photograph of the cross-sectional thickness of the Cu-Ni film prepared in Example 1 of the present invention.

[0016] Figure 3 It is an enlarged cross-sectional view of the Cu-Ni film prepared in Example 1 of the present invention.

[0017] Figure 4 The Cu prepared in Example 1 of the present invention x Ni y Electron microscope image of (OH)2 nanowires.

[0018] Figure 5 The Cu prepared in Example 1 of the present invention x Ni y Enlarged image of (OH)2 nanowires.

[0019] Figure 6 The Cu prepared in Example 1 of the present invention x Ni y Electron microscope image of O nanowires.

[0020] Figure 7 3 is an electron microscope photograph of the Cu-Ni nanowires prepared in Example 1 of the present invention.

[0021] Figure 8 is a TEM image of the Cu-Ni nanowires prepared in Example 1 of the present invention.

[0022] Fig. 9 is a HR-TEM image of the Cu-Ni nanowires prepared in Example 1 of the present invention.

[0023] Fig.10 This is a scanning electron microscope and EDS image of the cross section of the Cu-Ni nanowire prepared in Example 1 of the present invention.

[0024] Fig.11 This is the XRD pattern of the Cu-Ni NWs prepared in Example 1 of the present invention. Fig.12 is the XRD pattern of Cu (111) peak.

[0025] Fig.13is the LSV diagram of Cu-Ni NWs prepared in Example 1 of the present invention.

[0026] Fig.14 is the Faradaic efficiency of Cu-Ni NWs.

[0027] Fig.15 is the Faradaic efficiency of Cu NWs.

[0028] Fig.16 is the current density of the Cu-Ni NWs and Cu NWs prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0029] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0030] Unless otherwise specified, the materials and reagents used in the following examples can be obtained from commercial sources.

[0031] In the following examples, the reagents were used as received without further purification. Copper sulfate (CuSO4, 99.99%), nickel sulfate (NiSO4, 99.99%), nickel chloride (NiCl2, 99.99%), potassium bicarbonate (KHCO3, 99.7%), and boric acid (H3BO3, 99.8%) were all provided by Sinopharm Chemical Reagent Company. Sodium sulfate (Na2SO4, 99%), sodium hydroxide (NaOH, 99%), citric acid (C6H8O7), ammonium persulfate (((NH4)2S2O8, 98%), hydrochloric acid (HCl, AR) and anhydrous ethanol (C2H5OH) were obtained from Aladdin reagent. Carbon dioxide (CO2, 99.999%), nitrogen (N2, 99.999%) and argon (Ar, 99.999%) were used according to the received amount. Gas diffusion layer (GDL, hydrophobic carbon paper, Sigracet 22 BB) and anion exchange membrane (3PK-130) were purchased from Gauss Associates. Ultrapure water with a resistivity of 18.45 MΩ cm was prepared in the laboratory.

[0032] In the following examples, the electrochemical test method is as follows: Electrochemical tests were performed in a flow electrolysis cell at ambient temperature. The flow electrolysis cell is a three-electrode cell with three compartments. 3PK-130 was used as an anion exchange membrane to separate the anode and cathode, Ag / AgCl electrode (KCl saturated, salt bridge) was used as the reference electrode, 1 M KOH was used as the electrolyte, iridium oxide mesh (3 × 1 cm) was used as the counter electrode, and the working electrode was fixed to the size of 2 × 0.5 cm with a spacer. CO2 flowed into the gas chamber at a rate of 30 sccm and diffused through the gas diffusion layer into the cathode, where electroreduction occurred at the gas-liquid-solid three-phase interface. The outflowing gas products were sampled at fixed intervals (15 min) and quantitatively analyzed using GC. A peristaltic pump was used to assist the circulation of the catholyte (10 mL / min) and the anolyte (40 mL / min). The electrochemical reaction data were collected using a CHI760E electrochemical workstation, and the Faradaic efficiencies of the liquid and gas products were calculated based on the collected charge information (see the test details in the Supporting Information). All electrochemical tests used solution resistance to compensate for IR drop and converted all potentials to RHE values. Linear sweep voltammetry was performed at a scan rate of 20 mV / s.

[0033] Example 1. Preparation of Cu-Ni NWs A hydrophobic carbon paper (1×3 cm) was washed with anhydrous ethanol and 0.5 M HCl aqueous solution, respectively. The clean carbon paper was rinsed with ultrapure water and the support layer of the carbon paper was protected with a cover tape. Then, the carbon paper was immersed in a mixed solution of 0.1 M CuSO4, 0.07 M NiCl2, and 0.03 M NiSO4 (0.1 M citric acid buffer) and electrodeposited for 1500 s. The obtained carbon paper covered with Cu-Ni film was thoroughly dried under nitrogen atmosphere.

[0034] The carbon paper covered with Cu-Ni film was placed in 100 mL of aqueous solution containing 4.8 g NaOH and 2.282 g (NH4)2S2O8. The mixture was then allowed to react at 5 °C for 30 min. After thorough washing and drying, a blue hydroxide was obtained. Subsequently, the sample was annealed in a muffle furnace at 200 °C for 2 h to form a black oxide. In a flowing electrolytic cell, 0.50 M sodium sulfate solution was used as the electrolyte and a potential of -1.0 V (vs Ag / AgCl sat.KCl) was applied for electrochemical reduction to obtain an in-situ grown Cu-Ni alloy nanowire gas diffusion electrode.

[0035] Example 2. Characterization of Cu-Ni NWs GDEs prepared by catalyst ink coatings have difficulty in taking advantage of their inherent advantages, suffering from problems such as hindered CO2 mass transfer, slow electron transport, and insufficient exposure of catalytic active sites, leading to suboptimal CO2RR results. In contrast, nanoarray electrodes constructed in situ on GDLs can promote fast CO2 and charge transport, thereby significantly enhancing the reaction kinetics.

[0036] In Example 1 of the present invention, a Cu-Ni alloy film is constructed on a GDL by electrodeposition as a precursor of a nanowire structure ( Figure 1 The cross-sectional image shows that the deposited alloy film is distributed on the outer surface of the GDL with a thickness of approximately 6.95 μm ( Figure 2 and Figure 3 ). The continuous and uniform films ensure their electrical connection with the carbon paper substrate. Under alkaline conditions, the Cu-Ni alloy film is converted into Cu x Ni y (OH)2 nanowires ( Figure 4 and Figure 5 ). By annealing Cu in a muffle furnace x Ni y (OH)2 to obtain Cu x Ni y O nanowires ( Figure 6 Subsequently, CuO was in situ electrochemically reduced to Cu-Ni alloy nanowires (Cu-Ni NWs) in a flow electrochemical cell ( Figure 7 ).

[0037] The one-dimensional linear structure of Cu-Ni NW was confirmed by transmission electron microscopy, and its width was about 65 nm ( Figure 8 In addition, HR-TEM showed that Cu NWs were composed of nanocrystals exhibiting different crystal orientations, abundant grain boundaries within the structure indicated that the surface was full of defects, and the abundant microporous structure facilitated the mass transfer process of CO2 ( Fig. 9 ). Cross-sectional SEM image ( Fig.10 ) showed that after nanoscale processing, Cu-Ni NWs were uniformly distributed on the GDL surface without obvious gaps or cracks, showing good adhesion on the GDL substrate. EDS images also supported this result. Compared with the nanowire / GDL electrode prepared by catalyst ink coating, the abundant open spaces between the in-situ constructed nanowires on the GDL facilitated the diffusion and adsorption of reactants on the catalyst surface and promoted fast charge transfer, significantly enhancing the CO2RR reaction kinetics.

[0038] The crystal composition of Cu-Ni NWs samples was determined by X-ray diffraction (XRD) patterns ( Fig.11). Cu-Ni NWs exhibit diffraction peaks similar to those of standard copper (ICDD No. 98-000-0172), corresponding to the (111), (200), and (220) planes of copper. Compared with the original Cu NW, the peaks of CuO and Cu2O corresponding to air oxidation in Cu NW disappear due to Ni doping. The more chemically active nickel prevents the oxidation of Cu NW, a phenomenon consistent with the behavior observed in Cu-Ni corrosion-resistant alloys.

[0039] In addition, due to the low Ni loading and relatively weak crystallinity, no diffraction data of the Ni phase are shown. Fig.12 In the graph, it is observed that the Cu(111) peak of Ni-Cu NW shifts slightly to a higher diffraction angle and is located between the standard peaks of Cu(111) and Ni(111). This is attributed to the incorporation of Ni atoms into the Cu crystal phase, which produces lattice strain and proves the formation of alloy.

[0040] Example 3. Electrocatalytic CO2 Performance of Cu-Ni NWs The Ni-Cu NWs were loaded onto a flow cell using 1 M KOH as the electrolyte to rigorously evaluate the CO2 electroreduction activity properties.

[0041] Before starting the tests, all samples were subjected to an activation process, which included 20 cyclic voltammetry (CV) from 0 to -1 V (vs. RHE). Cu NWs in situ loaded onto GDL under the same conditions served as a control group for consistent experimental evaluation. Initially, each catalyst was subjected to linear sweep voltammetry, which was performed in both Ar and CO2 atmospheres to ensure a comprehensive analysis.

[0042] like Fig.13 As shown, it is observed that the reaction start time of Cu-Ni NWs is earlier than that of Cu NWs, and the current density is significantly greater than that of Cu NWs, which indicates that the Cu-Ni NWs of the present invention have faster adsorption and electrochemical reaction of CO2 and promote the accelerated kinetics of CC coupling.

[0043] The efficacy of CO2RR was evaluated by applying electrode potentials ranging from −0.7 V to 1.2 V (vs. RHE). The gas phase products were analyzed by online gas chromatography (GC). The distribution of the main products FE of different catalysts is shown in Figure 2. Fig.14 and Fig.15 Cu-Ni NW achieved the highest C2H4 selectivity (46.98%) at -1 V, and the current density reached 231.81 mA / cm 2 ( Fig.16). Cu NWs achieved a carbon product Faradaic efficiency of 56.11% at an applied potential of -1.0 V. However, Cu NWs showed poor selectivity, with relatively uniform distribution of CO (25.62%), CH4 (14.88%), and C2H4 (16.99%), without obvious dominant products, and poor selectivity.

[0044] Compared with bare Cu NWs, Cu-Ni NWs exhibit significantly enhanced C2H4 selectivity, demonstrating the catalytic advantage of the alloy nanowires.

[0045] In contrast, the Cu-Ni interface material in thin film form produced only ~18% formate product.

[0046] The three-dimensional nanoarray structure of the present invention provides abundant active sites, greatly enhancing the mass transfer process and promoting CC coupling kinetics. This is also attributed to the synergistic interaction between Cu and Ni atoms, which creates a favorable environment for accelerating chemical transformation.

Claims

1. A method for preparing Cu-Ni alloy nanowires, comprising the following steps: S1, immersing carbon paper in a mixed solution of CuSO4, NiCl2, and NiSO4 for electrodeposition to obtain a Cu-Ni film; S2, the Cu-Ni film reacts under alkaline conditions to obtain Cu-Ni hydroxide nanowires; S3, annealing the Cu-Ni hydroxide nanowires to obtain Cu-Ni oxide nanowires; S4. The Cu-Ni oxide nanowires are electrochemically reduced to obtain in-situ grown Cu-Ni alloy nanowires.

2. The preparation method according to claim 1, characterized in that: In step S1, the mixed solution is prepared from a citric acid buffer solution.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, in the mixed solution, the concentration of CuSO4 is 0.05M-0.15M, the concentration of NiCl2 is 0.03M-0.08M, and the concentration of NiSO4 is 0.03M-0.08M.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In step S1, the electrodeposition time is 1500-2000s.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In step S2, the alkaline condition is an aqueous solution of NaOH and (NH4)2S2O8, the concentration of NaOH is 45-50 g / L, and the concentration of (NH4)2S2O8 is 20-25 g / L.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In step S2, the reaction temperature is 2-8°C and the reaction time is 0.3-0.6h.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In step S3, the annealing temperature is 150-200° C. and the time is 0.5-2 h.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In step S4, the electrochemical reduction is performed in a flowing electrolytic cell using a sodium sulfate solution as an electrolyte.

9. Cu-Ni alloy nanowires prepared by the method according to any one of claims 1 to 8.

10. Use of the Cu-Ni alloy nanowires according to claim 9 as gas diffusion electrodes in the electrochemical reduction of CO2 to produce ethylene.

Citation Information

Patent Citations

  • Method for improving catalytic performance of NiCu alloy through electrochemical oxidation

    CN114150345A

  • Preparation method of carbon fiber loaded copper-nickel alloy nanoparticle nitrate ammonia conversion catalyst

    CN115449835A

  • Preparation method and application of nickel-modified copper-based monatomic alloy oxide nanowire

    CN118292028A

  • Preparation and application of rod-like nano-array composite copper material

    CN118422261A

  • NANO-TWINNED Cu-Ni ALLOY LAYER AND METHOD FOR MANUFACTURING THE SAME

    US20230220517A1